Effect of supplementation continuously in pullet and early lay period with Bacillus subtilis and yeast cell wall on the intestinal morphology, bone parameters, and egg quality of hens - Gao, Hang; Xiao, Jinzhi; Zhang, Qi; Man, Hutianlin; Tang, Xingyi; Wang, Zhouyuan; Fang, Rendong; Jiang, Sha (Frontiers in Veterinary Science, 2025)
The aim of this study was to investigate effect of Bacillus subtilis (BS), yeast cell wall (YCW), and their combination on intestinal and bone development and egg production of young hens. A total of 160, one-day-old Hy-Line Sonia chicks were randomly allocated into 4 treatments of 8 replicate cages of 5 birds each. Treatments were arranged in a 2 (0 and 0.5 g/kg of BS) × 2 (0 and 2 g/kg of YCW) factorial arrangement for a duration of 170-d as follows: (1) regular diet (Control group); (2) the regular diet plus 0.5 g BS/kg (BS group); (3) the regular diet plus 2 g YCW/kg (YCW group); and (4) the regular diet plus 0.5 g BS/kg and 2 g YCW/kg (BS + YCW group). One bird from each of the 8 replicate cages per treatment were randomly taken for sampling at d 110 and 170, respectively. Results indicated that there were different effects of BS and YCW on bird organ development and innate immune. YCW supplementation increased thymus index and serum concentrations of IgM of hens (p < 0.05). In addition, an interaction was observed between YCW diet and age on serum IL-6 concentrations (p < 0.05), mainly because YCW birds had the highest serum IL-6 concentration at d 110. Dietary supplementation with BS reduced the crypt depth in the duodenum and jejunum with an increased ratio of villus height to crypt depth (p < 0.05) in the duodenum, jejunum, and ileum. However, a YCW × age interaction on the jejunal villus height existed, mainly because non-YCW diet had the lowest jejunal villus height at d 170 (p < 0.05). Both BS and YCW enhanced egg weight, eggshell thickness and yolk color (p < 0.05), while YCW improved albumen height and Haugh unit (p < 0.05). There was no treatment effect on measured bone parameters except that YCW birds had lager tibial diameter (p < 0.05) at d 170. The results indicate that dietary BS and/or YCW improve the intestinal and bone development and immune status of young hens, which may contribute to the increased egg quality during the early sexual maturity stage.